After Abu Dhabi: Restoring Integrity and Accountability in Formula 1 - Zheng, Alice S. (The Columbia Journal of Law & the Arts, 2024)
By any metric, Sir Lewis Hamilton is one of the greatest drivers in Formula 1 history. With seven World Championship titles, 103 race victories, 104 pole positions, and 197 podiums under his belt to date, he continues to perform after nearly two decades at the pinnacle of motorsport. For many fans, the exciting aspect of a sport comes from the spectacle of competition, where regular people can watch an elite group of athletes fight for the title under a set of strict guidelines that are designed to promote fairness and offer a chance for any competitor to win. This veneer of a level playing field is shattered, however, when the very people put in charge to ensure accountability are the ones who contravene the established rules. Formula 1, with its flashy cars and highspeed racing, is no stranger to excitement and controversies. But the 2021 season brought to light certain aspects of the sport’s regulations and governance structure that many fans were unaware of, but which sit at the heart of the sport. The 2021 Abu Dhabi Grand Prix ended the 2021 Formula One World Championship in a dramatic and controversial fashion. Mercedes’ Lewis Hamilton and Red Bull’s Max Verstappen went into the final round with an equal number of points scored for the World Drivers’ Championship. The race was decided in the final few laps after Williams’ Nicholas Latifi crashed into the barriers with five laps remaining. After the safety car was deployed, Verstappen pitted for a fresh set of soft tyres, while Hamilton stayed out to maintain track position. On the second-to-last lap, Race Director Michael Masi directed only the five lapped cars between Verstappen and Hamilton to unlap themselves, in direct contravention of established Fédération Internationale de l'Automobile (FIA) rules. On the final lap, the green flag was deployed and the race resumed; Verstappen overtook Hamilton on his fresher tyres and maintained the lead, going on to win the Grand Prix and consequently the World Drivers’ Championship. Mercedes initially filed protests for breach of sporting regulations, but eventually withdrew them, citing a loss of faith in racing and that what happened in Abu Dhabi was "not right." This Note will clarify the problems with the current self-governing system utilized by FIA by examining the level of external versus internal decision-making and accountability systems, including the current judicial remedies offered by FIA. I will specifically examine the substantive discretion accorded to the Race Director and stewards to dictate the events of each Grand Prix, and what avenues are available to drivers and teams when a dispute arises that involves actions by the stewards. Namely, I will address the inadequacies of an organization attempting to police itself using its own appeals system. I will compare the governing structure and dispute resolution mechanisms used by FIA with the structures used by Major League Baseball (MLB) and the Fédération Internationale de Football Association (FIFA). I will then offer three potential methods of introducing external accountability to FIA—the Court of Arbitration for Sport (CAS) arbitration, MLB arbitration, or civil justice—and ultimately recommend CAS arbitration to FIA for adoption.